Vegetative Filter Strips—A Best Management Practice for Controlling Nonpoint Source Pollution - Lei Wu; Rafael Muñoz-Carpena; Yuncong Li (EDIS)
Increasing numbers of pollutants have been observed in natural water systems. As awareness of agricultural sources of water pollution has grown, Best Management Practices (BMPs) have been specifically designed to address agricultural water pollutants and protect water quality. This 4-page fact sheet introduces one of the BMPs, Vegetative Filter Strips (VFSs), which efficiently control nonpoint pollution such as sediments, nutrients, and pesticides. The publication covers primary functions, key design factors, and maintenance of VFSs. Written by Lei Wu, Rafael Muñoz-Carpena, and Yuncong Li, and published by the UF Department of Soil and Water Science, October 2015.